Are wheat-based farming systems in South Asia feminizing? - Farnworth, Cathy Rozel; Gartaula, Hom Nath; Badstue, Lone B.; Roeven, Lara; Bharati, Preeti; Rahman, Siddiqur; Petesch, Patti; Jafry, Tahseen (Frontiers Media, 2023)
This article pulls together the state of knowledge on the degree to which wheat-based systems in Bangladesh, India, Nepal, and Pakistan, are feminizing. It is not yet possible to make definitive statements. However, it is clear that wheat-based systems are undergoing far-reaching changes in relation to “who does what” and “who decides.” There are some commonalities across all four countries. Intersectionalities shape women’s identities and abilities to exert their agency. Purdah is a cultural norm in many locations. Nevertheless, each country displays different meta-trends. In Nepal managerial feminization is increasing unlike in Pakistan. Women in Bangladesh spend the least time in field work whereas in other countries they are often strongly engaged. There are strong local variations within countries as well which we explore. Establishing the extent of feminization is challenging because studies ask different questions, operate at different levels, and are rarely longitudinal. Researchers often construct men as primary farmers, leading to a failure to find out what men and women really do and decide. This diminishes the value of many studies. Cultural perceptions of honor can make men respondents reluctant to report on women’s agency and women can be reluctant to claim agency openly. We provide suggestions for better research, and urge support to women as workers and decision-makers.